Pengembangan Robot Humanoid Pemain Bola Otonom - Afrisal, Hadha; Munadi, Munadi; Faris, Muhammad; Ardi Sumbodo, Bakhtiar Alldino (TEKNIK, 2019)
This research aims to develop an autonomous humanoid soccer robot. The humanoid soccer robot is designed using 20 joints which are equipped with dynamixel servo motor AX-12 (upper body) and RX-24 (lower body) and is controlled by using servo controller board CM-700 (ATMega2561). The humanoid soccer robot is 44 cm in height and is equipped with a balancing system of using gyro sensor LPR530 and accelerometer KXM52-1050. In order to detect object and to navigate autonomously, the humanoid soccer robot is equipped with a CMOS camera which is controlled using CMUCAM board (LPC2016). The experiment shows that the humanoid soccer robot has ability to walk with average speed of 14.37 cm/second and is able to achieve a top speed of up to 20 cm/second. The developed humanoid soccer robot can play soccer autonomously: to locate the ball, to detect the goalpost, and to score the goal to the goalpost.